Herramienta para la estimación de costos basada en los renglones de pago del CR-2010, para el primer programa de la red vial cantonal PRVC-Préstamo BID No.2098/OC-CR, MOPT-GIZ - Araya-Paniagua, María Isabel (Instituto Tecnológico de Costa Rica, 2015)
In the present work an analysis of the cost estimating tools used by the consulting agency GIZ (for its acronym in German Deutsche Gesellschaft für Internationale Zusammenarbeit) is made, which works for the MOPT (Ministry of Public Works and Transport) in a program called First program Cantonal Road Network PRVC-Loan BID-No.2098 / OC-CR, MOPT-GIZ, also a new tool for estimating costs as an alternative to the problems encountered option is provided. Some of the activities were conducted studies and assessments to identify weaknesses that have used spreadsheets also select the information to include in their databases, this tool allowed developing cost estimates through Excel. The tool was carried out, using as reference manuals made by ombudsmen MOPT and CONAVI (National Roads Authority). The machinery specialist book called "Contractor's Equipment Cost Guide; MOPT interviews with experts and GIZ were also used. The main and most important conclusion was, obtaining calculation tool, gathering the information obtained throughout its development, as the recommendation to appoint a supervisor to ensure upgrades and implementations was also obtained, which should applied to existing tools and proposals. Keywords:
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2015.
Keywords: Manual de especificaciones; Estimación de costos; Indicadores económicos; Evaluación de rendimiento; Banco Interamericano de Desarrollo; Red vial